Advances in diabetes intervention: Targeting hormonal regulation, hIAPP, glucose transport, and key enzymatic pathways - Sari, Mulia Safrida; Lestari, Lilla Puji; Imun, Meri M.; Sriyanti, Cut; Ramli, Nurlaili (STKIP Persada Khatulistiwa Sintang, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from impaired insulin secretion or action. This condition remains a leading cause of global morbidity and mortality and is closely associated with various metabolic complications and cancer risk. This study aimed to identify potential molecular targets and hormonal regulatory mechanisms involved in diabetes management. A systematic review was conducted by searching indexed scientific articles in databases such as ScienceDirect and Google Scholar using the keywords “diabetes,” “molecular targets,” “insulin sensitivity,” and “hormonal regulation.” The analysis identified six major molecular mechanisms contributing to improved insulin action and glucose homeostasis, involving targets such as human islet amyloid polypeptide (hIAPP), ?-glucosidase, dipeptidyl peptidase-4 (DPP-4), sodium-glucose co-transporter-2 (SGLT2), glucose transporter type 4 (GLUT4) translocation, RNA-binding proteins (RBPs), and key enzymatic pathways associated with glucose metabolism. The development of therapeutic approaches directed toward these pathways could significantly enhance diabetes control, improve insulin sensitivity, and prevent long-term complications.